Functional Impairment of Murine Dendritic Cell Subsets following Infection with Infective Larval Stage 3 of Brugia malayi - Sharma, Aditi (Infect Immun, 2016)
Filarial parasites cause functional impairment of host dendritic cells (DCs). However, the effects of early infection on individual DC subsets are not known. In this study, we infected BALB/c mice with infective stage 3 larvae of the lymphatic filarial parasite Brugia malayi (Bm-L3) and studied the effect on fluorescence-activated cell sorter (FACS)-sorted DC subsets. While myeloid DCs (mDCs) accumulated by day 3 postinfection (p.i.), lymphoid DCs (LDCs) and CD8(+) plasmacytoid DCs (pDCs) peaked at day 7 p.i. in the spleens and mesenteric lymph nodes (mLNs) of infected mice. Increased tumor necrosis factor alpha (TNF-α) but reduced interleukin 12 (IL-12) and Toll-like receptor 4 (TLR4), -6, and -9 and reciprocal secretion of IL-4 and IL-10 were also observed across all DC subsets. Interestingly, Bm-L3 increased the expression of CD80 and CD86 across all DC subsets but decreased that of major histocompatibility complex class II (MHC-II) on mDCs and pDCs, resulting in their impaired antigen uptake and presentation capacities, but maximally attenuated the T-cell proliferation capacity of only mDCs. Furthermore, Bm-L3 increased phosphorylated p38 (p-p38), but not p-ERK, in mDCs and LDCs but downregulated them in pDCs, along with differential modulation of protein tyrosine phosphatases SHP-1, TCPTP, PTEN, and PTP1B across all DC subsets. Taken together, we report hitherto undocumented effects of early Bm-L3 infection on purified host DC subsets that lead to their functional impairment and attenuated host T-cell response.